Cbl-b inhibitor NX-1607 activates MAPK/ERK signaling pathway and enhances T-cell activation - Ting Yu; Li Jia; Wenting Zhu; Shan Lu; Yongliang Zhang; Benjin Liu; Shanshan Song; Xubin Bao; Zehong Miao; Jinxue He (Journal for ImmunoTherapy of Cancer)
Backgroud: The E3 ubiquitin ligase casitas B lymphoma-b (Cbl-b) is pivotal in modulating immune responses by attenuating T-cell activation and cytokine production. Inhibiting Cbl-b presents a potential therapeutic strategy in immuno-oncology by enhancing immune activity.Methods: A rapid Homogeneous Time-Resolved Fluorescence (HTRF) assay was employed to evaluate the inhibitory efficacy of NX-1607 on Cbl-b. The effects of NX-1607 on T cell activation, cytokine production, and proliferation were characterized invitro using primary T cells and Jurkat T cells. A drug combination screening was performed utilizing the CD69 marker via flow cytometry to dentify signaling pathways involved in T cell activation by NX-1607. CRISPR/Cas9 technology was used to knock out PLCG1 and MAPK3/1 in Jurkat T cells, followed by the detection of p-PLCγ1 and p-ERK1/2 though Western blotting. The antitumor efficacy of NX-1607 was assessed in a murine model of A20 B-cell lymphoma using BALB/c mice, with subsequent flow cytometry analysis conducted to examine the phenotype of tumor-infiltrating lymphocytes (TILs).Results: Our data show that NX-1607 effectively inhibits Cbl-b activity at low nanomolar levels, boosting PLCγ1 and HCSL1 phosphorylation, activating MAPK/ERK signaling, and elevating CD69 expression. Inhibiting PLCγ1 and ERK1/2 significantly reduces NX-1607’s effect on T-cell activation. Oral administration of NX-1607 notably decreases tumor growth in the A20 B-cell lymphoma model, with immunophenotyping analyses of tumor-infiltrating lymphocytes revealing increased CD3+, CD4+, and CD8+ T cells in treated tumors. Furthermore, our results demonstrate that treatment with NX-1607 results in increased levels of phosphorylated PLCγ1 and ERK1/2 in circulating T cells.Conclusion: Taken together, these findings imply that the inhibition of Cbl-b by NX-1607 may enhance the activation of the MAPK/ERK signaling pathway, thereby sustaining T-cell activation. This provides compelling evidence for the molecular mechanism of NX-1607, underscoring the pivotal role of Cbl-b in controlling signal strength in T-cell activation after T-cell receptor (TCR) engagement.